IT project management practices in olympic summer Games-Rio2016 case study - Lima, F.; Sousa, M. J. (10th European Conference on Information Systems Management (ECIME 2016), 2016)
Olympic Summer Games is a well-known megaproject, which fascinates many people in the world, not only because of the sports, but as well as, for the management practices applied on its organization. Rio2016 is the first edition of The Olympics in South America and based on that the eyes of the world are on the project, especially to understand the readiness status of the city to host this multi-sport mega event and the planning processes and techniques, which have been applied on it. In the Organizing Committee of Olympic Games (OCOG) technology represents one of the most important pieces of this puzzle. Nowadays is almost impossible to have an event of this magnitude without technology support, and for this reason technology area has one of the highest budgets of the OCOG. Technology does not have, in general, a high rate of success in project management, but in this kind of project, there is not a second chance. It is mandatory to have a simple, trustworthy, and transparent project management practice implemented in the entire IT department able to provide quickly the required information to the executives to make decisions. This study intends to address the topic first doing a broad and deep literature review to gather the theory and methodological tools to support the researcher to evaluate the research findings. A case study in Rio2016 project was conducted to understand what kind of project management practices IT department has been applying and what the proportion of knowledge used from previous games is. Researcher could observed that Rio2016 IT department has been applying known project management practices based on PMI standard called PMBOK and in specific Olympics Games products, which means that a mix of project management artefacts have been supporting OCOG needs. Olympics do not have space neither a chance of failure that puts a high pressure on IT teams to manage their projects to achieve the goals agreed with IOC, partners, providers, and clients.